(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
Obesity is the main cause of lifestyle-related disease, which is in turn the main cause of death in Japan. Aerobic exercise is more effective than anaerobic exercise in burning body fat. The present study identified conditions that enhance the burning of body fat during aerobic exercise, including the effects of wearing support pants. Twenty-one young Japanese women completed aerobic exercise sessions while wearing each of three types of support pants. Total body fat burning during aerobic exercise was 16 times greater than that at rest. Partial-compression garments helped reduce body fat more efficiently than both non-compression and constant-compression pants.